Konsep Maslahah dalam Kepemimpinan Islam dan Implementasinya di Hidayatullah - Nashirul Haq (LPPM STIS Hidayatullah, 2022)
This research discusses the concept of Maslahah (public interest) in Islamic leadership and its implementation in Hidayatullah, an organization. The principle of al-maslahah guides leaders to base their policies and decisions on religious and worldly considerations. From a religious perspective, leaders are responsible for preserving the faith of the community, while from a worldly perspective, they must provide services and ensure the well-being of their people. Hidayatullah implements the concept of maslahah through various measures. Firstly, they change the organizational structure from a foundation to an Ormas (mass organization) and association to meet the organization's needs and development. They also make changes to the organizational structure, add new institutions, and alter institutional names, all with maslahah in mind. Additionally, they formulate a strong organizational identity as a guiding principle and establish the Basic Organization Guidelines (PDO) to prevent deviations and disputes. Lastly, Hidayatullah adopts a consultative approach by establishing organizational regulations through the Musyawarah Majelis Syura (consultative assembly). This ensures that differences of opinion are resolved and the regulations gain acceptance from all relevant parties. Through these steps, Hidayatullah aims to apply the concept of maslahah in its leadership, fostering harmony and preventing internal conflicts.